Bubble-assisted fabrication of hollow CoMoO4 spheres for energy storage. Issue 73 (28th August 2018) - Qu, Gan; Tian, Bingbing; Su, Chenliang; Tang, Yiwen; Li, Ying
Abstract : Hollow CoMoO4 spheres fabricated using a bubble-assisted strategy exhibit an exceptional electrochemical performance when applied in supercapacitors. Abstract : Herein, gas bubbles generated in situ from precursors assist the rapid construction of hollow sycamore fruit-like CoMoO4 spheres (HSCSs). This bubble-assisted fabrication strategy is easy to operate, ultra-fast, low cost and post-treatment-free, showing great potential for the large-scale production of HSCSs. The growth mechanism of HSCSs is discussed to reveal the evolution process, which may be generalized to the construction of a series of hollow ternary Mo-based oxides. The obtained HSCSs exhibit a superior specific capacitance and outstanding cyclic stability when applied in supercapacitors.